Postawa surrealistyczna, czyli w stronę "nowej, krytycznej hermeneutyki" - Kornhauser, Jakub (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The aim of this article is to discuss the crucial difference between the notions of ‘avant-garde’ (from Lyotard’s or Danto’s essays) and Perloff’s or Bolecki’s ‘modernism’ and to suggest a new, exclusive rather than inclusive, approach to literary studies, based on the experimental theory and poetics of Surrealism. This so-called “surrealist attitude” could be applied in the literary and cultural studies as a twofold paradigm: on the one hand, it focuses on the verbal or textual aspect of the avant-garde experiments (utilizing Bürger’s or Barthes’ theories), on the other hand, it gives an opportunity to acknowledge their anthropological or sociological character marked by Baudrillard, Danto, Foster, or Krajewski. In this perspective, the substantial process of abandonment of reality (Lyotard), which stands for the dominant element of the avant-garde aesthetics, could be connected with the crisis of represetation and with the binary nature of the objects (simultaneously, the textual/internal and contextual/exteral forms).